The development of framework for E-car rental services in UiTM Shah Alam / Noorazreen Ahmad - Ahmad, Noorazreen (2005)
A rental service is a service in which customers arrive to request the hire of a rental unit. It is more convenient than carrying the cost of owning and maintaining the unit. E-car rental service is a car hiring agent that based solely on the Internet. For these purpose, the development of framework for e-car rental services in UiTM Shah Alam are being developed to examine and identify the features of e-car rental service. A questionnaire has been produced as an instrument to assemble the data and 55 car rental website were observed. As regards, 53 features have been discovered in this research; which have been separated into two sections. Section A focuses on General Features and Section B on Specific Features. The outcome of this study will recommend and put forward the features that are vital for developing an e-car rental services for UiTM Shah Alam.